2016
DOI: 10.1155/2016/7345835
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Reticulocyte Count and Reticulocyte Hemoglobin Content as Predictors of Early Response to Exclusive Oral Iron in Children with Iron Deficiency Anemia

Abstract: We report data regarding kinetic of response to oral iron in 34 iron deficiency anemia children. Twenty-four/34 patients (70.5%) reached reference value of hemoglobin (Hb) concentration for age and sex at day + 30 from the beginning of treatment (complete early responders (CERs)), and 4/34 (12%) reached an Hb concentration at least 50% higher than the original (partial early responders (PERs)). CHr at T1 (within 7 days from the beginning of treatment) was significantly different in the different groups (22.95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
3
20
0
1
Order By: Relevance
“…20,32,33 On the contrary, the absolute reticulocyte count has been found to increase significantly within 7 days from the beginning of oral iron supplementation (2 mg/kg/day) in iron-deficient anemic children. 34 Our result confirms previous recommendations that all forms of iron supplementation within the previous 7 days must be recorded on the doping control form. 20 Such information should also be made available for experts upon evaluation of atypical passport findings according to WADA's requirements for the management of the ABP.…”
Section: Intra-individual Variationsupporting
confidence: 90%
“…20,32,33 On the contrary, the absolute reticulocyte count has been found to increase significantly within 7 days from the beginning of oral iron supplementation (2 mg/kg/day) in iron-deficient anemic children. 34 Our result confirms previous recommendations that all forms of iron supplementation within the previous 7 days must be recorded on the doping control form. 20 Such information should also be made available for experts upon evaluation of atypical passport findings according to WADA's requirements for the management of the ABP.…”
Section: Intra-individual Variationsupporting
confidence: 90%
“…Unfortunately, a similar association between a serum iron panel index and brain iron deficiency and dysfunction beyond the newborn period has yet to be determined. Reticulocyte Hgb content is the strongest predictor of iron deficiency and response to iron supplementation in children [ 47 , 48 ]. Unpublished studies in neonatal rats from our lab suggest that reticulocyte Hgb is a sensitive peripheral biomarker of impending brain iron deficiency.…”
Section: Screening and Treatment Strategiesmentioning
confidence: 99%
“…Previously, it was reported that Ret-He content is an early and accurate predictor of hematological response to oral iron therapy in children. 13 Few recent studies have also evaluated Ret-He content to assess latent iron deficiency and microcytic red blood cells in adult populations. 14,15 Chaipokam et al concluded that Ret-He content combined with reticulocyte and blood count is useful in evaluating microcytic red blood cells in Thai patients while Tiwari et al observed that Ret-He may be used in routine screening of latent iron deficiency in blood donors.…”
Section: Discussionmentioning
confidence: 99%